2012
DOI: 10.2304/ciec.2012.13.3.226
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cultural Artefacts in Play as Tools to Mediate Learning in an Intercultural Preschool Programme

Abstract: Starting with the research question 'What is the role of play as a means of genuine inclusion of home language and cultural traditions in an intercultural early learning programme?', the article focuses on the role of cultural artefacts in a programme in which the majority of the children were refugees from Africa. The sociocultural theory of learning of Vygotsky and the activity theory of Leontiev provided the theoretical framework for the study. From a sociocultural perspective, materials are cultural object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…As primary contacts with the families, they were also able to bring information from their home visits into these discussions. Finally, cultural artefacts, such as cooking and other kitchen utensils, baskets, and musical instruments (see Hennig & Kirova, 2012) brought into the classroom space by the FLFs and used on a regular basis by the children and the classroom staff were significant data sources, providing insights into cultural values and beliefs. The cultural brokers and FLFs were instrumental in obtaining informed consent for children's, parents' and community members' participation in the research aspect of the program.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As primary contacts with the families, they were also able to bring information from their home visits into these discussions. Finally, cultural artefacts, such as cooking and other kitchen utensils, baskets, and musical instruments (see Hennig & Kirova, 2012) brought into the classroom space by the FLFs and used on a regular basis by the children and the classroom staff were significant data sources, providing insights into cultural values and beliefs. The cultural brokers and FLFs were instrumental in obtaining informed consent for children's, parents' and community members' participation in the research aspect of the program.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…In contrast, in the classroom in which the study took place, the facilitators, drawing on their personal relationships with the families, were able to bring in the same cultural artefacts the children would have seen at homesuch as traditional slings, rattles, kitchen implements, and cradles-to support the children's play. These artefacts served as cultural tools, mediating the children's learning in a manner which resonated with home (Hennig & Kirova, 2012). Figures 1 and 2 show the children preparing to put the baby to sleep in the cradle, and carrying the baby in it.…”
Section: Knowledge Of Home Realities and Traditionsmentioning
confidence: 99%
“…In this way, the culture broker acknowledges issues of social power and privilege in the science classroom. In a bicultural study of African refugee children learning in Canadian elementary and early childhood schools, Hennig and Kirova (2012) and Kirova (2010) reported that culture brokers brought African artifacts and other materials from African culture to help the refugee children learn in a context of their African culture while in a different continent away from Africa. The children learned creatively and were able to learn English when using their cultural materials without difficulty.…”
Section: Theoretical Support For Consideration Of Turkana Cultural Knmentioning
confidence: 99%
“…Rekindling curriculum is an example of a cross-cultural pedagogy that creates bridges to facilitate smooth border crossing between Western culture and indigenous cultural perspective. Humanistic, collateral, and culture brokers argue for smooth border crossing in bicultural and multicultural education (Aikenhead, 2001;Aikenhead & Jegede, 1999;Hennig & Kirova, 2012;Kirova, 2010).…”
Section: Theoretical Support For Consideration Of Turkana Cultural Knmentioning
confidence: 99%
“…Cultural brokers were instrumental in animating and interpreting children's behaviors and learning in the classroom from a cultural lens. For instance, observation and participation in daily home activities such as cooking was natural for many of the children in the program, some of whom had limited exposure to many of the play items found in a traditional early learning classroom (see Hennig & Kirova, 2012; Kirova 2010 for a description of play and cultural artifacts in intercultural early learning).…”
Section: Co-constructing Knowledgementioning
confidence: 99%